Fall time may be a reliable discriminator between neoplastic and non‐neoplastic urinary bladder lesions in dogs undergoing contrast‐enhanced ultrasound: a pilot study. Issue 5 (9th June 2022) - Spediacci, Carlotta; Manfredi, Martina; Sala, Giulia; Liuti, Tiziana; Israeliantz, Nicolas; Zani, Davide Danilo; Di Giancamillo, Mauro; Longo, Maurizio
Abstract: Contrast‐enhanced ultrasound (CEUS) can provide quantitative information on enhancement patterns and perfusion of lesions, based on time‐intensity curves (TICs). No published studies have compared CEUS parameters in neoplastic and non‐neoplastic urinary bladder lesions in dogs. The aim of the current prospective, pilot study was to quantitatively characterize the CEUS pattern of neoplastic and non‐neoplastic urinary bladder lesions in dogs, assessing the influence of contrast arrival time (CAT) on the final appearance of the curves. Fourteen dogs with cyto‐histopathological diagnoses were included (seven malignant and seven inflammatory lesions). B‐mode ultrasound was performed followed by CEUS examination after an intravenous bolus injection of 0.04 mL/kg of contrast medium, and TICs were elaborated by dedicated software. Receiver operating characteristic curves (ROC) for each TIC parameter were obtained. Neoplastic lesions had subjectively shorter rise time (RT), time to peak (TTP) and fall time (FT) than inflammatory lesions. Based on ROC curve analyses, fall time ≥ 10.49 s was the most reliable parameter for diagnosing non‐neoplastic disease in this small sample of dogs (area under the curve [AUC] 0.75, sensitivity 83.33%, specificity 66.67%). No difference was found between ROCs calculated for each parameter of TICs by adding or removing CAT. Results of the current study provide background for future, larger scale studies evaluating use of a CEUS FT threshold of 10.49 s as a possible discriminator for urinary bladder neoplastic lesions in dogs.